Study of load carrying mechanism of a novel three-pad gas foil bearing with multiple sliding beams. (1st January 2020) - Li, Changlin; Du, Jianjun; Yao, Yingxue
Highlights: A novel three-pad gas foil bearing is studied, which has multiple sliding beams. The elaborate foil structural model is developed based on the contact mechanics. Predicted bearing load capacity and stiffness agree well with the test results. Frictional energy dissipation of the foil structure is discussed. Abstract: This paper studies the load carrying mechanism of a novel three-pad gas foil bearing. An elaborate model of the bearing foil structure is developed, in which the multiple supporting beams are able to slide with friction on the bearing sleeve. The area contact between the top and support foils as well as the rotor-top foil contact is also considered. Under different types of contact constraints, the nonlinear foil structural deformation is further coupled with the compressible Reynolds equation to obtain the aeroelastic solutions. The accuracy of the model is verified by the experimental study in which the test results of bearing load capacity and stiffness are in good agreements with the predictions. The simulation results indicate that, (i) the area contact between top foil and sliding beams increases the foil structural stiffness; (ii) thinner support foil and larger rotor preload can increase the frictional energy dissipation of the foil structure; and (iii) bearing load capacity and the aeroelastic characteristics are significantly influenced by the layouts and thickness of support foil.